An approach to the interpretation theories of the Constitution - Quispe Astoquilca, Carlos Luis (2017)
The present article is about the constitutional interpretation theories. In the introduction, the author gives us a general vision of the present debate aroused around them. “Is the interpretation that conditions Constitution or is the Constitution that conditions interpretation?” comes to be the central question proposed by the article. To reach a possible answer, the author guides us through the world of constitutional interpretation theories, analyzing each one exhaustively and concluding with a new proposition about a general theory of constitutional interpretation, using the most important elements of each one of the theories previously exposed.